A Comprehensive Program Evaluation of a Mindfulness-Integrated English for Academic Communication Course - I Made Perdana Skolastika; I Wayan Heka Arcana Putra; I Kadek Purnawan (STKIP AGAMA HINDU SINGARAJA, 2026)
This study evaluates a mindfulness program integrated into the English for Academic Communication (EAC) course at Universitas Mahasaraswati Denpasar, aimed at enhancing students' academic communication skills and emotional well-being. Guided by the Context, Input, Process, and Product (CIPP) evaluation model, the research examines how mindfulness practices support learner development in an English as a Foreign Language (EFL) context. A qualitative design was employed, incorporating document analysis, classroom observations, and semi-structured interviews with 60 students across two classes and one course lecturer. Thematic analysis generated findings across all four CIPP dimensions. In terms of context, the program aligned well with both institutional goals and students' emotional and academic needs. Regarding input, available resources and instructor preparation were deemed sufficient to support effective delivery. At the process level, implementation was carried out consistently, though limited class time and varied student participation were noted as challenges. In terms of product, students reported improvements in emotional regulation, academic confidence, and self-awareness; reflective journaling and guided mindfulness exercises were identified as particularly beneficial in fostering metacognitive awareness. Overall, the findings suggest positive perceived effects on students' ability to manage anxiety and apply communication strategies in academic settings. The study concludes that embedding mindfulness-based, student-centered approaches within language instruction promotes both academic competence and emotional resilience. Future iterations of the program are recommended to incorporate more interactive, technology-supported mindfulness tools to sustain engagement and address diverse learner needs.